PERAN R20 DAN BENTUK KRITIK TERHADAP SEKULARISASI - Dewa Putu, Bhagastya Dharma; Ni Putu, Ayu Gita Shanti Pratiwi; Pattalala, Keisha Patricia (Sekolah Tinggi Agama Islam Kuningan, 2024)
The diversity of human beliefs becomes a fertile ground for building a strong voice in political competition. The fusion of religion and politics to achieve a goal creates various conflicts because these two elements should not be combined while carrying the idea of secularism. Secularism focuses on separating political interests from religious interests. In this research, we focus on R20, which is an activity that invites various heads of state and religious leaders, not only focusing on religious issues, but also on global conflicts such as environmental, economic, social, and political issues. This research adopts a qualitative method with data collection from online literature. Through this method, the research aims to explain the R20 activities that have been carried out as an effort to criticize the idea of secularism, which seeks to exclude religion from the political aspect. The implementation of R20 proves that no matter how strong the desire is to separate religion and politics, it should not be forgotten that these two aspects will always coexist, whether it is politics based on religious teachings or religion that drives politics. Keywords : Secularism, Religion, Politics, R20